Preparation and Compatibility of EVM/TPU Blend - Shi, Xinyan; Zhang, Ping; Liang, Yicong; Ren, Chunlian; Zhao, Shugao (Journal of macromolecular science. Physics, 2007)
The preparation of EVM (ethylene-vinyl acetate copolymer rubber)/TPU (thermoplastic polyurethane) blends with various ratios and their compatibility were investigated. The influence of mixing technology, filler type and content, the VA content in EVM (40 and 70 wt.%) and the addition of compatibilizers on the mechanical properties and the compatibility of the EVM/TPU blends were systematically studied. The test results showed that in preparation of the blend, fillers should be added to the blend to improve the processability and that among the fillers used, silica showed the best reinforcing effect on the blends. The best parameters for blending EVM and TPU in a HAAKE rheometer was: mixing temperature 160°C, rotor speed 45 rpm and mixing time 15 min. The test results also showed that the compatibility of EVM 700 (VA=70%) with TPU was better than that of EVM400 (VA=40%). The addition of a compatibilizer EVM-g-MAH and EVM-g-FME improved the processability of the blends. The addition of EVM-g-MAH also improved the compatibility of EVM 700/TPU blend; both the mechanical properties and hot-air aging properties of the blends were improved. However, the addition of EVM-g-FME did not improve the compatibility of EVM/TPU blends.